2001
DOI: 10.1080/00268970110042613
|View full text |Cite
|
Sign up to set email alerts
|

o-Terphenyl: flips of the end rings in the crystal phase

Abstract: We demonstrate by selective saturation deuteron NMR experiments on a crystal of selectively deuterated o-terphenyl (OTP) that both end rings I and II attached to the central ring undergo thermally activated flip motions. In crystals of OTP, the end rings I and II are not symmetry related, their dynamics can be different and, in fact, is different, although mutual steric hindrance of the rings suggests a strong correlation. We measured the rates k I and k II of the flips of both end rings I and II as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…51 kJ mol -1 in a penicillin salt to ca. 111 kJ mol -1 in another pencillin derivative 20 and many other examples such as para-iodo-benzene, biphenyl, or other compounds [18][19][20][21][22][23][24][25][26] displaying activation energies between these two extremes. The activation energy of the π flips of the phenyl ring in solid TEE is thus one of the lowest activation barriers for this kind of dynamic disorder in organic solids observed so far.…”
Section: Resultsmentioning
confidence: 99%
“…51 kJ mol -1 in a penicillin salt to ca. 111 kJ mol -1 in another pencillin derivative 20 and many other examples such as para-iodo-benzene, biphenyl, or other compounds [18][19][20][21][22][23][24][25][26] displaying activation energies between these two extremes. The activation energy of the π flips of the phenyl ring in solid TEE is thus one of the lowest activation barriers for this kind of dynamic disorder in organic solids observed so far.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, also small organic molecules are not as rigid as commonly believed. This has been demonstrated not only for the rotation of the methyl group in toluene [12], but also for the phenyl rings in O-terphenyl [13,14]. From the comparison of different chlorotoluene supercooled liquids it has been concluded that the origin of the secondary relaxation of that glass is mainly due to the rotation of the CH 2 Cl subgroup [15].…”
Section: Nature Of the Secondary Relaxationmentioning
confidence: 87%
“…An extensive theoretical introduction to CODEX can be found in the literature [15]. Note Added in Proof: After completion of this work we learnt about a recent study by Haeberlen et al, [16] who detected phenyl flips even in the crystal phase of o-terphenyl.…”
Section: Methodsmentioning
confidence: 97%